independence of the central banks with a focus on measuring the independence of the central bank of Jordan - جميل, هيل عجمي; رسمي, رنا (Journal of Economics and Administrative Sciences, 2015)
The main topic of this study is central around the independence of Jordanian central bank and the extent of the effectiveness at the bank in leading the monetary policy without interferences or pressures from side of the government.  the degree of independence of Jordanian central bank was  based on the following based hypothesis following ,there is relationship between the independence of the central bank and the legislative and economical indices. the most important recommendations are degree of independence of the Jordan central bank 43.5% is a good one, but it possible to reach a higher degree than this one by to making some modification on the Jordanian central bank law and by the central bank should be more rigid in relation to lending to government